FACTORS RELATED TO DIETARY BEHAVIOR OF POLYPHARMACY OF THE POPULATION AGED 35 YEARS AND OVER IN NONG CHIM SUB-DISTRICT NOEN SA-NGA DISTRICT CHAIYAPHUM PROVINCE - ไพรวงษ์, ชัญญานุช; เพ็งแจ่ม , ณัฐวัลย์; แก้วชิณ , พรทิพย์; หอมอยู่ , ธวัชชัย (Primary Health Care Journal (Northeastern Edition), 2022)
This research is a cross-sectional analytical study. The objectives of this study were to study factors related to drug consumption behavior of the population aged 35 years and over, Nong Chim sub-district, Noen Sa-nga district Chaiyaphum province. The samples were drawn from a population of 381 Krejcie and Morgan tables by simple random sampling. The research tool was a questionnaire created by the researcher. Data were analyzed by descriptive statistics such as percentage, mean, and standard deviation. Inferential statistics were mean estimation in one population group, and the relationship was tested using Pearson's correlation coefficient statistic. The results showed that the population is knowledgeable about the consumption of the drug series, at a high level, 64.3% had attitudes about drug consumption. In the moderate level, 50.9% access to the consumption of the drug kit and the source of selling the drug kit at a high level, 80.3%. Social support in consuming a set of drugs moderate and the population has a set of drug consumption behaviors at a high level of 70.9%. Attitudes about drug consumption Accessibility of consuming kits and kits for sale and social support in consuming a set of drugs statistically significant (r = 0.232, 0.392, 0.215 and 0.413, P-value < 0.05).